Broadly neutralizing antibodies recognizing different antigenic epitopes act synergistically against the influenza B virus. Issue 1 (6th September 2022) - Zhai, Linlin; Zhang, Limin; Jiang, Yushan; Li, Baisheng; Yang, Minghui; Victorovich, Khrustalev Vladislav; Aleksandrovna, Khrustaleva Tatyana; Li, Mengjun; Wang, Yuelin; Huang, Dong; Zeng, Zhujun; Ren, Zuning; et al.
Abstract: The discovery of broadly neutralizing monoclonal antibodies against influenza viruses has raised hope for the successful development of new antiviral drugs. However, due to the speed and variety of mutations in influenza viruses, single‐component antibodies that recognize specific epitopes are susceptible to viral escape and have limited efficacy when administration is delayed. Hence, it is necessary to develop alternative strategies with better antiviral activity. Influenza B virus infection can cause severe illness in children and the elderly. Commonly used anti‐influenza drugs have low clinical efficacy against influenza B virus. In this study, we investigated the antiviral efficacy of combinations of representative monoclonal antibodies targeting different antigenic epitopes against the influenza B virus. We found that combinations of antibodies recognizing the hemagglutinin (HA) head and stem regions showed a stronger neutralizing activity than single antibodies and other antibody combinations in vitro. In addition, we found that pair‐wise combinations of antibodies recognizing the HA head region, HA stem region, and neuraminidase enzyme‐activated region showed superior antiviral activity than single antibodies in both mouse and ferret in vivo protection assays. Notably, these antibody combinations still displayed good antiviral efficacy when treatment was delayed. Mechanistic studies further revealed that combining antibodies recognizing different epitope regions resulted in extremely strong antibody‐dependent cell‐mediated cytotoxicity, which may partly explain their superior antiviral effects. Together, the findings of this study provide new avenues for the development of better antiviral drugs and vaccines against influenza viruses.